PENERAPAN SISTEM PAKAR DIAGNOSA SECTIO CAESAREA PADA IBU HAMIL BERBASIS ANDROID DENGAN MENGGUNAKAN METODE CERTAINTY FACTOR - Rici Surya Ardani Diningrat; Murni Marbun (Jurnal Sistem Informasi Kaputama (JSIK), 2022)
Pregnancy and childbirth are special things that are experienced by a mother who is a woman's nature. The normal birth process is the desire of many pregnant women, but sometimes each of these processes experiences disturbances or symptoms that endanger the mother and fetus and lead to the delivery of Sectio Caesarea. The diagnosis of Sectio Caesarea is usually carried out by a doctor who is an expert in his field, but sometimes consulting a doctor requires routine costs that must be incurred and preparation time according to the schedule determined by the doctor. Situations and conditions that do not allow direct consultation with a doctor due to the distance from home, or a doctor who is not always available will prevent pregnant women from providing treatment. This study aims to build an expert system application as an alternative solution to provide a diagnosis of the symptoms experienced as done by an expert such as providing explanations, diagnoses, and suggestions. The method used is the Certainty Factor method by looking for the certainty value of a fact. This expert system application was developed based on Android so that it is easy to use. The test is carried out by comparing the results of the system diagnosis with the results of expert diagnoses, the diagnosis is divided into 3 parts, namely fetal or maternal distress that is a life-threatening, fetal or maternal emergency that is not lifethreatening, delivery is required without any signs of fetal or maternal distress. The result show that the application of expert Sectio Caesarea diagnosis system can diagnose disorders symptoms experienced by pregnant women, as well solutions treatmens for these symptoms.